10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
INTRODUCTION: Although nasal structural and functional changes after total laryngectomy (TL) have been documented, the influence of clinical variables and symptoms remains underexplored. This study compared nasal structure and function between TL patients and healthy controls and identified clinical factors associated with these changes. METHODS: A cross-sectional study was conducted on male patients with laryngeal cancer post-TL and healthy male volunteers. Objective nasal assessments included the saccharin test for mucociliary clearance time (MCT), acoustic rhinometry for nasal volume and minimal cross-sectional area (MCA), and contractility index calculated from changes pre- and post-decongestant. Nasal symptom scores were also collected. RESULTS: Forty participants were enrolled (20 per group). Mean MCT was significantly longer in the TL group (10.99 ± 8.41 min) than in controls (6.69 ± 3.72 min; p = 0.047). Mean nasal volume and MCA were comparable between groups (p = 0.77 and 0.31, respectively), as were contractility indices (p = 0.13 and 0.64). Multiple linear regression revealed postoperative duration and smoking amount as significant predictors of increased MCA. Nasal symptoms were reported by 70% of TL patients. Dry nose was negatively correlated with changes in nasal volume and contractility index (r = -0.44 and -0.46, respectively). CONCLUSION: TL patients exhibited prolonged MCT despite no significant morphometric differences. Postoperative duration and smoking exposure were associated with increased MCA, suggesting potential confounding. Reduced nasal contractility was associated with dry nose symptoms. Overall, these findings suggest an effect of nasal airflow deprivation on nasal physiology and may inform future targeted interventions.